2021 IEEE 29th International Conference on Network Protocols (ICNP) 2021
DOI: 10.1109/icnp52444.2021.9651930
|View full text |Cite
|
Sign up to set email alerts
|

Is Machine Learning Ready for Traffic Engineering Optimization?

Abstract: Traffic Engineering (TE) is a basic building block of the Internet. In this paper, we analyze whether modern Machine Learning (ML) methods are ready to be used for TE optimization.We address this open question through a comparative analysis between the state of the art in ML and the state of the art in TE.To this end, we first present a novel distributed system for TE that leverages the latest advancements in ML. Our system implements a novel architecture that combines Multi-Agent Reinforcement Learning (MARL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Ryu et al [19] build a nearest neighbor graph to form homogeneity within the agent adjacencies. Similarly to our work, [15], [17] extract the agent embedding without modeling the system adjacencies directly. From an algorithmic perspective, [13], [16], [17] introduced attention mechanism in GNN for extracting agent state embedding.…”
Section: Related Workmentioning
confidence: 98%
“…Ryu et al [19] build a nearest neighbor graph to form homogeneity within the agent adjacencies. Similarly to our work, [15], [17] extract the agent embedding without modeling the system adjacencies directly. From an algorithmic perspective, [13], [16], [17] introduced attention mechanism in GNN for extracting agent state embedding.…”
Section: Related Workmentioning
confidence: 98%
“…Since communication networks are fundamentally represented as graphs, GNNs offer unique advantages for network modeling when compared to traditional NN architectures (e.g., multilayer perceptron, recurrent NN). In the last years, GNNs have demonstrated outstanding performance to solve a wide variety of network-related problems [2], [6], [10], [5], [11]. In this context, GNNs may be a central technology to enable the construction of ML-based network models that can generalize to different network topologies, configurations, and traffic distributions.…”
Section: A Leveraging Machine Learning To Build Ndtsmentioning
confidence: 99%
“…Moreover, RouteNet has shown its ability to precisely infer characteristics of input (e.g., topology) unseen in the training [8]. Especially, in [9], the authors have shown a novel integration of GNNs into a Deep Reinforcement Learning (DRL) framework to solve routing problems by which trained models are capable of inferring solutions for unseen testing topologies. Comprehensive machine learning approaches to graph combinatorial optimization problems, including GNN design for several algorithms are presented in [10].…”
Section: Related Workmentioning
confidence: 99%